The influence of tutoring and learning motivation on mathematics achievement of junior high school students - Jehadus, Emilianus; Tamur, Maximus; Chen, Jihe; Perbowo, Krisna Satria (Universitas Papua, 2022)
Many factors influence student academic achievement, including tutoring and learning motivation. This research aimed to describe the influence of tutoring and learning motivation on Year 8 students’ mathematics achievement in one of the junior high schools in Ruteng, Indonesia in the academic year of 2019/2020. This descriptive research with survey design involved 66 students. Data were collected by administering a student questionnaire consisting of 20 questions. The 5-point Likert scale questionnaire used in this research focused on two categories: tutoring and learning motivation. The final semester test scores were used as the data on students' achievement in learning mathematics. The results revealed that the two factors were positively related to students' mathematics achievement; both contributed to student achievement by 18.49%. These findings confirm that tutoring and students’ motivation from teachers or parents are essential because both mediate student achievement. These results provide meaningful knowledge about the importance of teachers or parents providing structured tutoring to support the mathematics achievement of junior high school students.